Relation between innovative work behavior and ethical climate perceptions among nursing personnel - Nagwa Gouda Ahmed Abd-Elmoghith; Amal Sobhy Mahmoud; Aida Mahmoud Abdel-Azeem (BMC, 2024)
Abstract Background Globalization and innovative technologies forced organizations to adopt innovative approaches and innovations for gaining a sustainable competitive advantage. Innovative Work Behavior (IWB) is related to the employees, ability, and enthusiasm to create innovative ideas. It exhibits a dynamic framework that is easier to be impacted by the ethical climate. Methods Descriptive correlational design was applied and the study was performed at different inpatient units in Kafrelsheikh Governorate General Hospital. Two hundred twenty-two staff nurses and 45 head nurses from the aforementioned setting were chosen as a purposive sample. Two instruments were utilized to obtain the data; Innovative Work Behavior questionnaire and Ethical Climate Questionnaire. The significance of the acquired data was evaluated at the 5% level. Number and percentage were used to describe qualitative data and Range frequency, mean, standard deviation, and Pearson coefficient were used to characterize quantitative data. Results More than half of staff nurses had a positive perception of innovative work behavior and more than three quarters of them had a negative Ethical climate perception. Conclusion The study proved a significant relation between Efficiency dimension and the overall innovative work behavior perception p = 0.044, and the economic affairs and innovation dimension and the overall ethical climate perception p = 0.033.